Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1534/genetics.112.145912
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Inference Reveals African and European Admixture in the North AmericanDrosophila melanogasterPopulation

Abstract: Drosophila melanogaster spread from sub-Saharan Africa to the rest of the world colonizing new environments. Here, we modeled the joint demography of African (Zimbabwe), European (The Netherlands), and North American (North Carolina) populations using an approximate Bayesian computation (ABC) approach. By testing different models (including scenarios with continuous migration), we found that admixture between Africa and Europe most likely generated the North American population, with an estimated proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
330
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(357 citation statements)
references
References 51 publications
(64 reference statements)
22
330
3
Order By: Relevance
“…It is therefore reasonable to assume that positive selection could have a substantial confounding effect on a variety of population genomic methods for demographic inference in practice, beyond those considered here. In the empirical literature, numerous recent studies of demographic history have found support for contractions and recent expansions of natural populations (Thornton and Andolfatto 2006;Fagundes et al 2007;Gravel et al 2011;Tennessen et al 2012;Duchen et al 2013). While such population size changes are probably common, and our results do not call the major findings of these studies into question, they do suggest that natural selection can exaggerate the inferred intensity of these changes.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…It is therefore reasonable to assume that positive selection could have a substantial confounding effect on a variety of population genomic methods for demographic inference in practice, beyond those considered here. In the empirical literature, numerous recent studies of demographic history have found support for contractions and recent expansions of natural populations (Thornton and Andolfatto 2006;Fagundes et al 2007;Gravel et al 2011;Tennessen et al 2012;Duchen et al 2013). While such population size changes are probably common, and our results do not call the major findings of these studies into question, they do suggest that natural selection can exaggerate the inferred intensity of these changes.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, C and D of Figure S8 suggest that the extent of exponential growth during the recovery phase is underestimated when very recent sweeps have occurred. Thus, we find that positive selection can dramatically skew population size histories deduced by PSMC.Positive selection produces spurious support for nonequilibrium demographic historiesDemographic inference methods are often used not only to infer parameters of a model, but increasingly to select the best fitting among several competing models (e.g., Adams and Hudson 2004;Fagundes et al 2007;Duchen et al 2013).To ask whether positive selection might affect the outcome of demographic model selection, we simulated genomes with constant population size, again sampling loci for which some fraction, f, is located within c/s # 1 of a selective sweep. We then performed model selection among our four demographic histories ( Figure 1) using both @a@i and ABC (Methods).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This species originated in sub-Saharan Africa, and approximately 10,000-15,000 years ago a subpopulation expanded out of the ancestral range. During this expansion, the derived subpopulation experienced a population bottleneck that resulted in decreased nucleotide polymorphism, extended linkage disequilibrium within the derived population and substantial genetic differentiation between ancestral and derived populations [2,[35][36][37][38][39]. Hereafter, the ancestral population will be referred to as "African" and the derived population as "Cosmopolitan".…”
Section: Introductionmentioning
confidence: 99%
“…Following this bottleneck, descendant populations of African and Cosmopolitan D. melanogaster have admixed in numerous geographic regions [2,11,21]. Of particular relevance to this work, North America was colonized recently by a population descendent from African individuals from the South, and by a population descendent from cosmopolitan D. melanogaster in the North [11,21,38]. Where these populations encountered each other in eastern North America, they form an ancestry cline where southern populations have a greater contribution of African ancestry than northern populations [21].…”
Section: Introductionmentioning
confidence: 99%